Historical and Cultural Consciousness in the Short Stories of Intezar Hussain - Kausar, Rehana; Hameed Khan, Shaista; Wakeel, Aiman (sourcecoder, 2022)
Intezar Hussain’s fiction is to analyze the situation in a logical way. His talk on visas and passports was in vogue in India and Pakistan, but now global moral contractors and preachers of tolerance are closing the doors of their country to the people out of love for their country. This is the form of blood in which even its shadow seems suspicious. These myths tell the historical situation of Pakistan. The themes of these myths describe the changes that have taken place in the social, cultural, civil and political spheres throughout history. The focus of their attention is our attitude towards the nation. Even superficial reactions to the greatest misfortunes and tragedies are astonishing.